1997
DOI: 10.1080/13614579709516911
|View full text |Cite
|
Sign up to set email alerts
|

Webbook for engineers: An interactive information skills programme

Abstract: First-year engineering students at the University of Queensland used an interactive webbook to acquire information skills. These helped them search information resources for their projects, which they are required to undertake as part of the subject Introduction to professional engineering. The information skills exercise was an integral part of the project and worth 10% of the overall assessment. The exercises were only available on the Web, allowing the students to enter their answers from home or wherever t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A typical pattern emerges. A package is created to support a subject-specific class (Orians and Sabol, 1996); or alternatively, a course in communications, professional or study skills provides a curriculum context for the library skills training (Parise, 1998;Cribb and Woodall, 1997). The academic level is undergraduate not research.…”
Section: A Pattern For Web/html Library Learning Materialsmentioning
confidence: 99%
“…A typical pattern emerges. A package is created to support a subject-specific class (Orians and Sabol, 1996); or alternatively, a course in communications, professional or study skills provides a curriculum context for the library skills training (Parise, 1998;Cribb and Woodall, 1997). The academic level is undergraduate not research.…”
Section: A Pattern For Web/html Library Learning Materialsmentioning
confidence: 99%
“…( Figure 1, Table 1). Of the 44 papers included quantitative [12], [20], [25], [30], [40]- [42], [46], [49], [50], [52], [54], [56]- [58], [63]; 14 qualitative [27]- [29], [33], [36], [37], [44], [45], [51], [53], [59], [61], [62], [65]; 11 mixed methods studies [18], [26], [31], [32], [38], [39], [43], [47], [48], [60], [66]; two literature reviews [34], [35]; and one instrument development paper [55]. The included studies were published between 1991 and 2018, having a median age of 5.5 years, and with five of the studies [28], [31], [36], [41],…”
Section: Resultsmentioning
confidence: 99%
“…The median sample size was 64 students. Several studies included students across different engineering disciplines, with breakdowns as follows: mechanical engineering undergraduates were the most frequently studied group (n=13) [12], [18], [30], [38], [41], [44], [45], [51], [53], [54], [57], [63], [66]; followed by first-year undergraduate engineers (n=10) [26]- [29], [32], [33], [36], [42], [47], [52], [59]- [62], [65]; civil (n=9) [12], [18], [37], [41], [49], [51], [57], [66]; electrical (n=6) [18], [41], [44], [51], [57], [66], computer (n=5) [20], [41], [50], [51], [66]. Limited demographic information was reported on the subjects; 12 studies reported the gender of participants [27], [28],…”
Section: Resultsmentioning
confidence: 99%